Ideologi, Bahasa dan Penyingkiran: Eksklusi Sosial Berbasis Bahasa yang Dihadapi Mahasiswa Asal Indonesia Timur di Pulau Jawa - Martha, Fajar (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study examines language-based social exclusion endured by migrant students from East Indonesia in Java. It applies and enriches Bracic's (2020, 2022) multidimensional exclusion cycle model by highlighting language's central role as a key dimension of exclusion in the Indonesian context, an area not yet fully elaborated within her theoretical framework. Analysis reveals that, beyond difficulties in formal and vernacular Indonesian, these students encounter discriminatory racial prejudice. This discrimination stems from a historical javanization process implemented by the Sukarno and Soeharto governments, leading to language hierarchization, structural racism, and racial discrimination. This research argues that language, ideology, and power are intertwined, perpetuating the exclusion cycle against these marginalized groups. This study used literature review and semi-structured interviews, and found the need for multidimensional interventions targeting language hierarchies, racial prejudice, and structural racism to break this exclusion cycle and foster equitable inclusion.